Efektifitas Mobilisasi Dini Pada Pasien Pasca Operasi Terhadap Mual Dan Muntah: Tinjauan Literatur - Delima, Descarina; Prabawati, Dewi (Jurnal Keperawatan Florence Nightingale, 2025)
Surgery is carried out diagnose or treat a disease, injury, disability and also treat conditions that are difficult or impossible to cure with medication only. However, several side effects maybe can occur after surgery and give dissatisfaction feeling in health care services. One of the complications that often occurs in post-operative patients is nausea and vomiting. Objective: This research aims to determine the effectiveness of early mobilization and what methods are used in its application. Method: Literature review research conducted on quantitative research articles using the PICOT data analysis process and thematic analysis method: a simplified approach.  Results: The use of the ERAS protocol is the most widely used mobilization method, with modifications according to the conditions where mobilization is gradual starting from the first post-operative day onwards. Early mobilization also can using ROM and other mobilizations that have been adjusted. The effectiveness of early mobilization is also influenced by other parties, such as providing simulations and guidance from nurses. Early mobilization carried out after surgery can reduce post-operative nausea and vomiting, help increase oxygenation, dan improve body function and reduce pain so that the recovery process can be faster.